PENGUKUHAN SOFT SKILL MAHASISWA CALON GURU PAI GENERASI GEN Z JURUSAN PENDIDIKAN DAN KEGURUAN UIN SUMATERA UTARA - Nur Aini Lubis; Nurul Fadillah; Arlina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Developments in information and communication technology have significantly influenced the characteristics of Generation Z students, including prospective Islamic Religious Education (PAI) teacher students. This generation is known to possess strong technological skills and access various information sources, but still faces various obstacles in mastering non-academic skills, or soft skills, which are highly needed in the world of education. This study aims to examine the urgency of strengthening soft skills for prospective Generation Z Islamic Religious Education (PAI) teacher students in the Islamic Religious Education Study Program, Faculty of Tarbiyah and Teacher Training, State Islamic University of North Sumatra, Medan. This study aims to identify the various challenges they face, and analyze strategies that can be implemented to develop them. The study used a qualitative approach with descriptive methods through observation, interviews, documentation, and literature review. The results indicate that communication, leadership, teamwork, time management, interpersonal skills, and problem-solving are soft skills that require special attention. The challenges faced by Generation Z students include high levels of digital technology use, reduced direct social interaction, minimal involvement in organizations, and the suboptimal implementation of soft skills development in the learning process. Efforts to strengthen soft skills can be implemented through integration into the curriculum, implementation of project-based learning, involvement in student organizations, training and seminars, mentoring programs, and improving digital literacy competencies. With continuous soft skills strengthening, prospective Islamic Religious Education (PAI) teachers are expected to become professional, character-driven, adaptive educators, and prepared to face the various challenges of education in the 21st century.